2015 International Conference on Signal Processing and Communication Engineering Systems 2015
DOI: 10.1109/spaces.2015.7058267
|View full text |Cite
|
Sign up to set email alerts
|

K enhancement of low contrast images using fuzzy techniques

Abstract: Most of images like medical images, satellite images and even real life photographs may suffer from poor contrast due to the inadequate or insufficient lighting during image acquiring. So there is a necessity of contrast enhancement of images. In this paper three enhancement techniques namely fuzzy rule based contrast enhancement, contrast enhancement using intensification (INT) operator, and contrast enhancement using fuzzy expected value (FEV) are presented for the low contrast grayscale images. Comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It was reported that the proposed approach can provide better results than those of the adaptive enhancement and linear stretching; it is revealed that the proposed technique gives much better results than the existing ones. Sudhavani et al [8] proposed a medical image enhancement technique of low-contrast images using fuzzy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the proposed approach can provide better results than those of the adaptive enhancement and linear stretching; it is revealed that the proposed technique gives much better results than the existing ones. Sudhavani et al [8] proposed a medical image enhancement technique of low-contrast images using fuzzy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This difference matrix works as a weight vector for perceptron network and the perceptron network is used to adjust the weight of input image or value. G. Sudhavani et al, [6] proposed three enhancement techniques namely fuzzy rule based contrast enhancement, contrast enhancement using intensification (INT) operator, and contrast enhancement using fuzzy expected value (FEV) are presented for the low contrast grayscale images. G. Sudhavani et al, [7] described the application of a modified fuzzy C-means clustering algorithm to the lip segmentation problem.…”
Section: Related Workmentioning
confidence: 99%
“…Good contrast images with preserving details are required for many important areas such as remote sensing, machine vision, biomedical image analysis, dynamic and traffic sense analysis, and autonomous navigation. However most of the recorded images suffer from low contrast, which is due to insufficient lighting during image acquiring, wrong setting of shutter speed and aperture size [6]. Thus, contrast enhancement is employed to increase contrast of the image.…”
Section: Introductionmentioning
confidence: 99%